Earnings Management Index, State Ownership, Industrial Sectors, and Timeliness of Financial Report in Indonesia - Shindy Anisa Putri; Y Anni Aryani (AKRUAL: JURNAL AKUNTANSI, 2020)
In recent years, IDX reported that a high number of enterprises financial reporting were overdue. Timeliness of financial report is necessary since it is used as the main source of information. This paper aims to investigate several factors affecting timeliness of financial report in Indonesia. Using the purposive sampling technique, this study gained 318 enterprises listed on IDX during 2015 until 2017. The result showed that earnings management index and industrial sector were significantly related to the timeliness of financial report. On the other hand, state ownership do not have significant relation with the timeliness of financial report.